The Curvilinear Relation between Work Predictability and Creativity. Issue 3 (3rd July 2022) - Caniëls, Marjolein C.J.; de Jong, Jeroen P.; Sibbel, Hannes
ABSTRACT: In this study, we investigate how the level of work control predictability affects employee creativity. Specifically, we examine whether supervisor and coworker support moderate the predictability-creativity relationship. We use survey data from 128 employee–supervisor dyads from a governmental organization in Belgium. Multilevel analyses demonstrated a significant inverted U-curve relationship between predictability and leader-rated creativity, indicating that too little or too much work control predictability contributes less to employee creativity compared to moderate levels of work control predictability. Moreover, supervisor and coworker support moderate this relationship in such a way that for employees who receive low support the inverted U-curve relationship is significantly stronger compared to employees that receive high support. This is the first study that focuses on work control predictability in relation to creative performance.